Oral or topical nasal steroids for hearing loss associated with otitis media with effusion in children. - Butler, C; Van Der Voort, J (2002)
BACKGROUND: Otitis media with effusion (OME) is common and may cause hearing loss with associated developmental delay. Treatment remains controversial. The effectiveness of both systemic and topical intranasal steroids in promoting the resolution of effusions has been assessed by randomised controlled trials. OBJECTIVES: To examine evidence for or against treating children with hearing loss associated with OME with systemic or topical intranasal steroids. SEARCH STRATEGY: Searches were conducted in January 2002. We searched the Cochrane Controlled Trials Register using the terms 'otitis media', 'otitis media with effusion', 'glue ear', or 'OME', and 'steroids', 'glucocorticoids, synthetic', 'glucocorticoids, topical', 'anti-inflammatory agents, steroidal'. EMBASE and MEDLINE were also searched for additional information. SELECTION CRITERIA: Randomised controlled trials of oral and topical intranasal steroids, either alone or in combination with another agent such as an antibiotic, were included. EXCLUSIONS: publications in abstract form only since adequate appraisal was not possible; uncontrolled, non-randomised or retrospective studies; studies reporting outcomes with ears (rather than children) as the unit of analysis unless data were of sufficient detail to allow analysis by child. DATA COLLECTION AND ANALYSIS: Data were extracted from the published reports by the two authors independently (CCB and JH van der V) using standardised data extraction forms and methods. The methodological quality of the included studies was independently assessed by the two authors using the scheme described in the Cochrane Handbook. Dichotomous results were expressed as an odds ratio using a fixed effects model together with the 95% confidence intervals. Continuous data were analysed using the weighted mean difference in a fixed effects model. Tests for heterogeneity between studies were performed using a Mantel-Haenszel approach. In trials with a cross over design, post crossover treatment data were not used. MAIN RESULTS: No study prospectively documented hearing loss associated with OME prior to randomisation. Follow up was mainly short term. No serious or lasting adverse effects were reported in the six studies that did mention adverse effects. Most comparisons involved small numbers of subjects. The odds ratio for OME persisting after short term follow up in children treated with oral steroids compared to control was 0.22 (95% CI 0.08 to 0.63). The odds ratio for OME persisting after short term follow up for children treated with oral steroids plus antibiotic compared to control plus antibiotic was 0.32 (95% CI 0.20 to 0.52). However there was significant heterogeneity between studies included in the latter comparison (p<0.01). Trends favoured steroids for most other comparisons, but confidence intervals included unity. There was no evidence of benefit for steroid treatment for resolution of OME or of resolution of hearing loss associated with OME in the longer term. REVIEWER'S CONCLUSIONS: Both oral and topical intranasal steroids alone or in combination with an antibiotic lead to a quicker resolution of OME in the short term. However, there is no evidence of a long term benefit from treating OME effusions or associated hearing loss with either oral or topical intranasal steroids. No serious adverse events were reported in the six studies that presented data on adverse effects. Future studies should document hearing loss associated with OME before the start of study treatment. Follow up should be longer and ideally include health related quality of life and hearing assessments. Data should not be presented only with ears as the unit of analysis.